Estimation of nonadditive genetic impacts on lifetime performance through a grading-up breeding program with Holstein-Friesian - Zsolt Nemes; Vitomir Vidović; Dragomir Lukač ;; Ante Ivanković; Goran Grubić; István Komlósi; András Gáspárdy (Mljekarstvo)
The aim of this study was to estimate the total lifetime milk production and non additive genetic effects (recombination and heterosis) of cows with different proportions of Holstein-Friesian genes, obtained from the Serbian Fleckvieh (SF) and the Holstein-Friesian (HF) crossbreeding program in Vojvodina. Upgrading of local breeds with the Holstein-Friesian breed in Vojvodina started in 1971 and continued 2008. Six genotypes of cows (F1, R1, R2, R3, R4, R5) were obtained with increasing percentage of Holstein genes, in order to attain purebred Holstein cows. Of all obtained genotypes, cows of genotype R4 with a proportion of Holstein genes from 96.87 % had the highest lifetime milk production (20000 kg), followed by cows R3 with 19950 kg (93.75 % HF genes) and cows R5 with 19850 kg (98.44 % HF genes). Finally the process of upgrading resulted in pure Holsteins with 19780 kg of milk. The total lifetime production of milk fat did not show statistically significant difference (P>0.05) among the genotypes R1 - R5 which ranged from 675 to 690 kg. The pure Holstein obtained after sixth intermediate generations had the average lifetime milk fat production of 690 kg. With the increase in the proportion of Holstein-Friesian genes percentage of milk fat was decreased, so that the cows of genotypes R3, R4, R5 and pure Holsteins, had less than 3.5 % milk fat. In relation to the total milk yield, the highest realized heterosis effect was observed in the cows of F1 generation (hRF1=594 kg), while the lowest was observed in generation R2 (hRR2=72 kg), where negative effect of recombination was also found (hIR2=-77 kg). Positive values of the actual and relative of heterosis effect of the milk fat yield was observed in all genotypes, whereas the negative heterosis effect of the milk fat percentage was observed also in all genotypes, with the exception of R1 and R2 cows, in which the typical consequence of the positive recombination in the early crossed Holstein-generations was manifested.